Comparison Between Linear Stapler and Circular Stapler After Laparoscopic-Assisted Distal Gastrectomy in Patients With Gastric Cancer - Sun, Danping; Zhang, Renhua; Wei, Meng; Liu, Peng; Zhong, Xin; Liang, Yize; Chen, Yuanyuan; Huang, Yadi; Yu, Wenbin (Frontiers in Surgery, 2022)
Background and Aim To evaluate the safety and efficacy of laparoscopy distal gastrectomy using a linear stapler compared with a circular stapler in patients with gastric cancer. Methods We retrospectively reviewed 173 patients who underwent laparoscopic distal gastrectomy for gastric cancer at a single center from January 2018 to December 2020. Patients were categorized into the linear stapler group and the circular stapler group. General data, intraoperative and postoperative outcomes, postoperative pathological results, postoperative complications, and postoperative follow-up in the two groups were compared and analyzed. Results The operation time (208.76 ± 32.92 vs. 226.69 ± 26.92 min, p < 0.05), anastomosis time (71.87 ± 9.50 vs. 90.56 ± 3.18 min, p < 0.05), time to first flatus (68.60 ± 25.96 vs. 76.16 ± 21.05 h, p < 0.05), time to the first sip of water (3.66 ± 0.61 vs. 4.07 ± 0.77 days, p < 0.05), and time to the first liquid diet (4.43 ± 1.02 vs. 5.03 ± 1.70 days, p < 0.05) were significantly shorter in the linear stapler group. In addition, the highest postoperative body temperature within 3 days (37.4 ± 0.61 vs. 37.7 ± 0.61, p < 0.05) after the operation, white blood cell count (WBC) on the 3rd day (9.07 ± 2.52 vs. 10.01 ± 2.98 × 10∧9/L, p < 0.05), and average gastric tube drainage within 3 days (36.65 ± 24.57 vs. 52.61 ± 37 ml, p < 0.05) were also significantly lower in the linear stapler group. Conclusions Both circular and linear staplers are safe and feasible for gastrointestinal reconstruction in laparoscopic distal gastrectomy. In contrast, a linear stapler has advantages over a circular stapler in shortening operation time and accelerating the postoperative recovery of patients.